2019
DOI: 10.1016/j.invent.2018.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Adapting an internet-delivered intervention for depression for a Colombian college student population: An illustration of an integrative empirical approach

Abstract: BackgroundCulturally adapted psychotherapy (CAP) studies are limited and until now there are few published examples that illustrate the process of cultural adaptation with internet-delivered treatments.AimThis paper aims to illustrate an integrative approach to the cultural adaptation of an evidence-based internet-delivered cognitive-behavioural therapy intervention for depression (Space from Depression programme).MethodMixed method approach utilising quantitative and qualitative methods to assist in the cultu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 83 publications
2
35
0
Order By: Relevance
“…Arjadi and colleagues ( 33 ) applied the Ecological Validity Model to adapt an internet-based behavioral activation intervention addressing depression for Indonesian people. In addition, an internet-based intervention for depression was culturally adapted for Colombian university students using this model ( 34 ) and was evaluated ( 35 ). Evidence from a meta-analysis of eight randomized controlled trials showed that the effectiveness of minimally guided digital mental health interventions to reduce symptoms of common mental disorders was enhanced by cultural adaptation ( 36 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Arjadi and colleagues ( 33 ) applied the Ecological Validity Model to adapt an internet-based behavioral activation intervention addressing depression for Indonesian people. In addition, an internet-based intervention for depression was culturally adapted for Colombian university students using this model ( 34 ) and was evaluated ( 35 ). Evidence from a meta-analysis of eight randomized controlled trials showed that the effectiveness of minimally guided digital mental health interventions to reduce symptoms of common mental disorders was enhanced by cultural adaptation ( 36 ).…”
Section: Introductionmentioning
confidence: 99%
“…The current study adopted the EVM ( 26 ) to inform which intervention elements should be culturally adapted. The framework, including eight culturally sensitive dimensions (i.e., language, persons, metaphors, content, concepts, goals, methods, context) was previously applied in cultural adaptation studies ( 20 , 22 , 34 ). For the framework informing the strategies and process of cultural adaptation, the current study did not follow any existing cultural adaptation process model ( 22 , 37 , 38 ) since they were not appropriate for digital mental health program as digital mental health interventions minimize contact between the providers and service users.…”
Section: Introductionmentioning
confidence: 99%
“…The culturally adapted version of the PM+ intervention protocol was assessed by a Colombian and a Venezuelan psychologist, both based in academic institutions, who independently evaluated the protocol using the Cultural Relevance Questionnaire (CRQ), in approximately 3 h [36]. Grounded in cultural sensitivity and ecological validity theories and principles, the CRQ was specifically developed to evaluate the degree of ecological validity following cultural adaptation [2,37].…”
Section: Settingmentioning
confidence: 99%
“…Previous reviews and meta-analyses have summarised studies that conducted IMI in LMIC [53] and investigated the extent and effectiveness of cultural adaptation of IMI for the treatment of common mental disorders among people with diverse cultural backgrounds [48]. Yet, the procedure of the cultural adaptation is often only poorly reported [43,52,[54][55][56]. This makes it difficult to identify components of the cultural adaptation that may contribute to an enhanced acceptance and effectiveness of IMI, such as the language, illustrations, or example characters [43,54,56,57].…”
Section: Introductionmentioning
confidence: 99%